High-quality entangled photon source by symmetric beam displacement design - G. Paganini; Á. Cuevas; R. Camphausen; A. Demuth; V. Pruneri (APL Photonics)
Entangled photon sources (EPSs) are pivotal in advancing quantum communication, computing, and sensing. The demand for deploying efficient, robust EPSs in the field, characterized by exceptional (phase) stability, has become increasingly apparent. This work introduces a polarization-entangled photon source, leveraging type-0 spontaneous parametric downconversion and constructed using commercial bulk optomechanical components. Our system is versatile, enabling the generation of N00N states for sensing applications or Bell states for quantum key distribution protocols. We attained a maximal Bell inequality violation, with the average entanglement visibility exceeding 99%. The potential for further performance enhancements is also explored.